Managing innovation in the development of new products (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
The I + D process is profitable, although implies risks. It is necessary for a corporate sustainable growth, as it meets customer needs. Managers should monitor this process strictly but with a certain degree of flexibility to face unforeseen circumstances.Companies must remain open minded to enter into new businesses whenopportunities are detected.
Keywords: Innovation activity; sustainable growth; consumer needs; new opportunities.